Accelerometer systems as tools for health and welfare assessment in cattle and pigs – A review - Chapa, Jose M.; Maschat, Kristina; Iwersen, Michael; Baumgartner, Johannes; Drillich, Marc (Behavioural processes, 2020)
•We discuss the validity of specific behavioural patterns measured by accelerometers.•Welfare assessment studies based on accelerometer technology are provided.•Aspects to be considered before application of accelerometer systems are discussed.•We present ideas for the future application of accelerometers in welfare assessment. Welfare assessment has traditionally been performed by direct observation by humans, providing information at only selected points in time. Recently, this assessment method has been questioned, as ‘Precision Livestock Farming’ technologies may be able to deliver more valid, reliable and feasible real-time data at the individual level and serve as early monitoring systems for animal welfare. The aim of this paper is to describe how accelerometers can be used for welfare assessment based on the principles of the Welfare Quality assessment protocol. Algorithm development is based mainly on the detection of behavioural traits. So far, high accuracies have been found for movement and resting behaviours in cows and pigs, while algorithm development for feeding and drinking behaviours in pigs lag behind progress in cows where valid algorithms are already available. Welfare studies have used accelerometer technology to address the effects on behaviour of diet, daily cycle, enrichment, housing, social mixing, oestrus, lameness and disease. Additional aspects to consider before a decision is made upon its use in research and in practical applications include battery life and sensor location. While accelerometer systems for cows are already being used by farmers, application in pigs has mainly remained at the research level.